America's battalion : Marines in the first Gulf war - Lehrack, Otto J. (University of Alabama Press, 2005)
Tells the experiences of one unit, the 3rd Battalion, 3rd Marines, during Operation Desert Storm - the first Gulf War. Building from interviews with the members of the regiment, Otto Lehrack examines the nature of warfare in the Persian Gulf.